Design and experimental development of a compact and efficient range extender engine. (15th September 2017) - Borghi, Massimo; Mattarelli, Enrico; Muscoloni, Jarin; Rinaldini, Carlo Alberto; Savioli, Tommaso; Zardin, Barbara
Highlights: New concept of compact, clean and fuel efficient range extender engine. Developments through CFD simulation and experiments. Significant step forward in comparison to the current 4-strokes. Weight: −35%, brake efficiency: +6%, heat rejected: −18%, thermal load: −40%. Cost effective technology for CO2 reduction in transportation. Abstract: The paper reviews the design and experimental development of an original range-extender single-cylinder two-stroke gasoline engine, rated at 30 kW (maximum engine speed: 4500 rpm). The goal of the project is to get most of the benefits of the two-stroke cycle (compactness, high power density, low cost), while addressing the typical issues affecting the conventional engines of this type. Among many recent similar propositions, the peculiarities of this engine, besides the cycle, are: external scavenging by means of an electric supercharger, piston controlled scavenge and exhaust ports (no poppet valves), gasoline direct injection (GDI), and a patented rotary valve for the optimization of the scavenging process, of the loop type. Lubrication is identical to a conventional four-stroke engine, and the rotary valve, connected to the crankshaft, helps to improve the balance of the piston reciprocating forces, yielding an excellent NVH behavior. It should be noted that, except the patented rotary valve, all the engine parts are standard automotive commercial components, that don't require any specific expensive technology. In fact, the originality of the engine consists in the optimum combination of existing well assessed concepts. The scavenging and combustion systems of the engine are developed in the first phase of the project, including the construction and the experimental testing of a prototype. In the second phase, the air metering system of the prototype is completely modified: the piston pump is replaced by an electric supercharger, and engine load is now controlled by the supercharger speed, without throttle valve. The new engine is compared to a standard 4-stroke engine, developed in a previous project for the same application. The main advantages of the two-stroke engine may be summarized as follows: lower weight (−35%), higher brake efficiency (+6%, on average), less heat rejected (−18%), lower thermal and mechanical loads within the cylinder (−40%). The only concern, that will be addressed in a future phase of the study, is the compliance with very low NOx limits: in the worst scenario, the 2-stroke engine could be forced to adopt a well assessed but expensive after-treatment device.